Gastroesophageal reflux disease, resistant to proton pump inhibitors - V. O. Kaybysheva; A. S. Trukhmanov; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To discuss the factors, promoting development of resistance at treatment of gastroesophageal reflux disease (GERD), and possible means to overcome it.Original positions. Pharmacological therapy of GERD is focused on change of refluxate properties besides decreasing of its volume and aggressive properties by such classes of drugs, as antacids, alginates and hydrochloric acid secretion inhibitors. However for today frequency of clinical resistance in GERD patients reaches 10–40%. The causes of resistance to antisecretory therapy are inadequate acid suppression, weakly acidic refluxes, duodenogastroesophageal reflux, psychological features of patients, etc. Potentials of treatment of the patients with sustained symptoms of GERD on a background of standard dose of proton pump inhibitors (PPI), include correction drug intake, doubling of PPI dose, application of intravenous forms, combination of antisecretory agents of different groups, addition to therapy of drugs, capable to adsorb bile components and modulation of psychoemotional status of patients.Conclusion. Despite of significant progress in treatment of acid-related diseases the problem of resistance of significant part of GERD patients to antisecretory therapy is still actual.